ANALISIS PERTIMBANGAN HAKIM PENGADILAN TINGGI DALAM PUTUSAN NOMOR:37/2019.PT/DPS - NIM. A1012171112, ILHAM RAMADHAN (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac In this scientific work in the form of a thesis, the author gives the title, Analysis of the Judge's Consideration of the High Court in Decision Number: 37/2019.PT / DPS, is the author's effort to analyze the results of the Denpasar High Court Decision which has examined and tried civil cases at the appellate level, and has handed down a decision in the lawsuit case, namely strengthening the district court's decision that rejected all default claims of the Plaintiff against the Defendant. The author emphasizes the formulation of the problem in this study regarding the subject,